(untitled) (Fiep Bulletin - online, 2014)
The main objective of this research is the reflexive analysis of the current intervention in the classroom teaching of Physical Education, more specifically, the content sports collectives in the mode volleyball, 5th to 8th series in the public schools of the city of Guarapuava, PR. In view that the Physical Education quest adequately meet the needs driven, psychological, social and cultural rights of children and adolescents, it is important to the methodologies and goals of the Physical Education according to needs that is the very process of evolution of human beings to throughout its development. So, this search will be examined by means of questionnaires given to teachers of the public schools in this city, where the contents volleyball is being worked at the school in a way that meets a sequence of developments appropriate to the age and the heterogeneity of classes, in this mode under school.